Determine the Influence of Prenatal Stress on Fetal Development: LMRJ - Sharif, Anila (LIAQUAT MEDICAL RESEARCH JOURNAL, 2020)
Prenatal stress is an epigenetic factor which can produce long-lasting alterations in brain structures and body functions. The objective of this is to examine the ratio of prenatal stress among pregnant women. It is necessary to assess stress separately at each trimester of pregnancy to differentiate chronic from acute stress in order to evaluate the effect on child development. Prenatal stress can alter neurotropic growth factors, synapse development, neurotransmitter levels and also adult neuron development. Prenatal stresses significantly influence the development of the brain and the organisation of behaviour. Prenatal stress can also be the main cause of hypertension, type 2 diabetes, schizophrenia and cardiac disorders in adulthood. But the impact ofstress is not very clear. The survey based on a cross-sectional study was conducted in Karachi. The sample size calculated for the survey is 45. The pregnant women were asked to fill the questionnaire of 23 questions.